2000
DOI: 10.1053/rapm.2000.8574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 0.5% intrathecal bupivacaine with 0.5% intrathecal ropivacaine in the treatment of refractory cancer and noncancer pain conditions: Results from a prospective, crossover, double-blind, randomized study

Abstract: The results of this study do not support the hypothesis that IT infusion of 0.5% ROP has advantages over IT infusion of 0.5% BUP when administered for relief of "refractory" pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Systematic reviews, consensus conferences, and randomized controlled trials Three systematic reviews [5][6][7], three consensus conferences [8][9][10], and 12 RCTs [11][12][13][14][15][16][17][18][19][20][21][22] met the selection criteria of studies examining clinical effectiveness. Although the systematic reviews and consensus conferences included some relevant RCTs, no single systematic review or consensus conference included all relevant RCTs or sufficiently discussed the effectiveness of intraspinal analgesia for cancer-related pain to support recommendations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews, consensus conferences, and randomized controlled trials Three systematic reviews [5][6][7], three consensus conferences [8][9][10], and 12 RCTs [11][12][13][14][15][16][17][18][19][20][21][22] met the selection criteria of studies examining clinical effectiveness. Although the systematic reviews and consensus conferences included some relevant RCTs, no single systematic review or consensus conference included all relevant RCTs or sufficiently discussed the effectiveness of intraspinal analgesia for cancer-related pain to support recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…Intraspinal analgesia as an intervention was addressed in a summary of RCTs evaluating adjuvant analgesics. Three of the six RCTs were relevant [17][18][19]. The review concluded insufficient RCT evidence was available to determine the relative efficacy of the spinal versus systemic route of drug administration.…”
Section: Clinical Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Bupivacaine can also be used as the sole agent for ITA [61,67,142]. Moreover, it has been shown that the adjunction of bupivacaine to morphine leads to a diminished dose progression of morphine, suggesting a synergetic effect [251].…”
Section: Intrathecal Analgesia In Cancer Painmentioning
confidence: 99%
“…Local anesthetics are often used to alleviate pain after surgery, medical procedures and dental pains (Smith et al, 1999). They are also used in the control of postoperative pain and in the therapy of chronic pain (Dahm et al, 2000) and can be used for regional control of major pain. In relieving local pains, ropivacaine, one of local anesthetics belonging to the amide group, has been used.…”
Section: Introductionmentioning
confidence: 99%